PROSES PENYELESAIAN SOAL BERDASARKAN PEMAHAMAN POLYA PADAMAHASISWA DALAM MATA KULIAH KALKULUS VEKTOR - Rani Sugiarni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2019)
Vector calculus courses are active abstract subjects that students often have difficulty in understanding the material. The research method uses quantitative descriptive methods. In this study, the subjects were students of the Mathematics Education Study Program at Suryakancana University in the 7th semester of the 2017-2018 academic year in the subject of Vector Calculus. The data collection technique is done by using a question test instrument about Polya's comprehension ability. Based on the results of the conclusion analysis from Problem 3, it was seen that most students understood 85% of the presentations and for question number 5 was 67%. Problems no. 1a and 1b inductive ability seen that most students understood 82% and 85% inductive understanding abilities. Another thing understood by student number 2 shows that most students understand most with 70% presentation and for number 4 most students do not understand 48% presentation. Question number 6 shows that most students understand 88% and for number 7 most students understand 70%. From the overall indicators of Polya's ability from the results of the answers, the presuppositions of students' abilities in vector calculus courses are mostly in the category of not understanding and partial understanding. Students are still weak in finding the truth or proof of a certain formula of curvature.